2008
DOI: 10.2134/agronj2006.0345
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Olive Crop Yield in Andalusia, Spain

Abstract: All rights reserved. No part of this periodical may be reproduced or transmitted in any form or by any means, electronic or mechanical, including photocopying, recording, or any information storage and retrieval system, without permission in writing from the publisher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
35
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 21 publications
8
35
0
2
Order By: Relevance
“…Other species of the Oleaceae family, such as Fraxinus excelsior L. or F. angustifolia Vahl., also show variable quantities of pollen production per anther with 12500 grains for the former (Pohl, 1937) and 18 000-87 000 for the latter (Tormo Molina et al, 1996). In line with the data provided by Fornaciari et al (1997), Gómez-Casero et al (2004) or Galán et al (2008), our records confirm that temperature and precipitation are the variables, which mostly affect the pollen production of olive trees. According to our data, high values of maximum and minimum temperatures recorded during the pre-flowering months correlate inversely to the average production of pollen per anther.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Other species of the Oleaceae family, such as Fraxinus excelsior L. or F. angustifolia Vahl., also show variable quantities of pollen production per anther with 12500 grains for the former (Pohl, 1937) and 18 000-87 000 for the latter (Tormo Molina et al, 1996). In line with the data provided by Fornaciari et al (1997), Gómez-Casero et al (2004) or Galán et al (2008), our records confirm that temperature and precipitation are the variables, which mostly affect the pollen production of olive trees. According to our data, high values of maximum and minimum temperatures recorded during the pre-flowering months correlate inversely to the average production of pollen per anther.…”
Section: Discussionsupporting
confidence: 90%
“…The formation and maturation of pollen grains inside the anther is probably conditioned by genetic (Kaul, 1988) and environmental (García-Mozo et al, 2001) factors. Moreover, pollen production does indeed depend on the meteorological conditions during the preflowering period (Fornaciari et al, 1997;Galán et al, 2008), with temperature and precipitation, among other meteorological factors, playing a fundamental role in the process.…”
Section: Abstract: Environmental Effect Flower Production Rate Micrmentioning
confidence: 99%
See 1 more Smart Citation
“…Meiffren (1988) and Fornaciari et al (2000) have reported the ability of olea pollen to travel over middle and long distances. Indeed, the start and end date as well as the peak day of the pollen season can be influenced by the long-range transport phenomena of olive pollen from neighbour regions (Vázquez et al, 2003;Galan et al, 2004;Galán et al, 2008). Thus, several authors point out that phenological data should also be obtained in order to specify the aerobiological pollen season with respect to the local flowering in a more accurate way (Fornaciari et al, 2000;Garcıa-Mozo et al, 2009;Jato et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a number of studies have also used airborne pollen data as an indicator of climatic change or to create forecasting models for agricultural applications (Frenguelli, 1998;Newnham, 1999;Osborne et al, 2000;Emberlin et al, 2002;Van Vliet et al, 2002;Clot, 2003;Orlandi et al, 2005;Ribeiro et al, 2006;Galán et al, 2008;García-Mozo et al, 2008).…”
Section: Introductionmentioning
confidence: 99%